2017
DOI: 10.1111/1467-8322.12324
|View full text |Cite
|
Sign up to set email alerts
|

Heritage and participatory governance: An analysis of political strategies and social fractures in Spain

Abstract: In the heritage field, institutions tend to see social participation as a synonym for good governance practice. This extends to other areas such as the environment, humanitarian aid, and sustainable development. In this article, the authors analyze the use of participatory models in the management of heritage through the study of three heritage sites in Spain: the prehistoric paintings in Altamira, the Mosque‐Cathedral in Córdoba, and the Cabo de Gata‐Nijar Natural Park. Their study suggests that, despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 22 publications
0
8
0
4
Order By: Relevance
“…En este sentido, en la búsqueda del cumplimiento de uno de los objetivos de la RSC y su compromiso social, muchas empresas buscan que los colectivos sociales también participen. De esta forma, las empresas han encontrado una forma de legitimar sus acciones a través de diversas estrategias de participación social (Cortés-Vázquez et al, 2017).…”
Section: Las Normas Soft Law El Caso Concreto De La Norma Iso 26000 Y Su Referencia a La Igualdad De Génerounclassified
“…En este sentido, en la búsqueda del cumplimiento de uno de los objetivos de la RSC y su compromiso social, muchas empresas buscan que los colectivos sociales también participen. De esta forma, las empresas han encontrado una forma de legitimar sus acciones a través de diversas estrategias de participación social (Cortés-Vázquez et al, 2017).…”
Section: Las Normas Soft Law El Caso Concreto De La Norma Iso 26000 Y Su Referencia a La Igualdad De Génerounclassified
“…Research on cultural governance and participatory approaches to heritage has shown that democratisation can be a curse in disguise. Superimposed via international conventions, national regulations and White Papers, actions meant to improve access, use and management of heritage can work to hide social and bureaucratic dissonance under a goodwill blanket while pre-existent value regimes persist (Bendix et al, 2013;Corte´s-Va´zquez et al, 2017). This means that frameworks for public inclusion can, as in Denmark, be limited from within by the far-right.…”
Section: Working From the Insidementioning
confidence: 99%
“…The significance of governance for effective HM is highlighted (Shipley, 2008;Vázquez, 2017), yet only fragmented aspects are studied (Pickard, 2002;Blaug et al, 2006;EC, 2014;Saltiel, 2014). In fact, little attention is paid to investigating the whole governance system in the heritage sector.…”
Section: Introductionmentioning
confidence: 99%